Biology of Termites: a Modern Synthesis - Bignell, David Edward; Roisin, Yves; Lo, Nathan (Springer Netherlands : Imprint: Springer, 2011)
Biology of Termites, a Modern Synthesis brings together the major advances in termite biology, phylogenetics, social evolution and biogeography made in the decade since Abe et al Termites: Evolution, Sociality, Symbioses, Ecology became the standard modern reference work on termite science. Building on the success of the Kluwer book, David Bignell, Yves Roisin and Nathan Lo have brought together in the new volume most of the world's leading experts on termite taxonomy, behaviour, genetics, caste differentiation, physiology, microbiology, mound architecture, distribution and control. Very strong evolutionary and developmental themes run through the individual chapters, fed by new data streams from molecular sequencing, and for the first time it is possible to compare the social organisation of termites with that of the social Hymenoptera, focusing on caste determination, population genetics, cooperative behaviour, nest hygiene and symbioses with microorganisms. New chapters have been added on termite pheromones, termites as pests of agriculture and on destructive invasive species, and new molecular and cladistic frameworks are presented for clarifying taxonomy, especially in the higher termites which dominate many tropical ecosystems. Applied entomologists, developmental and evolutionary biologists, microbial ecologists, sociobiologists and tropical agriculture specialists will all benefit from the new insights provided by this work.